MEMBANGUN KARAKTER GENERASI MUDA HINDU DENGAN MENINGKATKAN KECERDASAN SOSIALMELALUI AJARAN TRI PARARTHA (Refleksi Perayaan Hari Raya Saraswati di Era Disrupsi) - Yadnya, Ida Bagus Gede Adi Putra (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
This paper is a reflection and meaning of the Saraswati day celebration in the midst of rapidly changing times. The occurrence of a generational change that results in a change in the way of thinking and a new way of working, demands also a quick adjustment. Speed of response is the key to success in the 21st century. Achieve success it requires another dimension besides the intellectual intelligence dimension. The dimension of social intelligence is one of the key components. Social intelligence is a person's ability to understand his environment optimally and react appropriately for social success. The point is to be able to win global competition, it is necessary to have a character that refers to aspects of social intelligence. One source of character values comes from the value of religious teachings. Hinduism has many important teachings that can be used as a reference in shaping the character of the younger generation, one of which is the teachings of Tri Parartha. This teaching describes three main attitudes and behaviors and aims to glorify others in the context of social interaction.